Turning Harmful Deposition of Metal Impurities into Activation of Nitrogen-Doped Carbon Catalyst toward Durable Electrochemical CO2 Reduction - Kim, Chanyeon; Choe, Yoong-Kee; Won, Da Hye; Lee, Ung; Oh, Hyung-Suk; Lee, Dong Ki; Choi, Chang Hyuck; Yoon, Sungho; Kim, Woong; Hwang, Yun Jeong; Min, Byoung Koun (AMER CHEMICAL SOC, 2019)
Electrochemical CO2 reduction is typically operated under highly refined electrolyte conditions. However, trace amounts of metal impurities exist even in ultrapure electrolyte solutions, causing a fatal deactivation of the catalysts. To address this issue, various efforts have been made to prevent the harmful deposition of metal impurities on the catalyst. Herein, we designed a new system where metal impurities are utilized as activators. We demonstrated "self-activation" of the N-doped carbon catalyst in the presence of Fe impurity with remarkable stability for 120 h. The origin of the self-activation was the selective adsorption of Fe impurity forming highly dispersed Fe sites through Fe-N interactions. The correlations between the self-activation and number of N sites and their moieties were investigated and further generalized into other metals, such as Ni, Zn, and Cu. This novel general strategy has enormous impact on design of durable catalysts for various electrochemical reactions suffering from deactivation by metal impurities.
Keywords: OXYGEN REDUCTION; PULSED ELECTROREDUCTION; DIOXIDE REDUCTION; ACTIVE-SITES; ELECTROLYTE; ELECTROCATALYSIS; DEACTIVATION; SIMULATION; MEMBRANES; ETHYLENE